Clinical value of quantitative analysis of Sonazoid-contrast enhanced ultrasound combined with shear wave elastography in discriminating and diagnosing breast tumor characteristics - Wang, Gang; Ouyang, Yingmei; Ruan, LiTao (Frontiers in Oncology, 2025)
ObjectiveThis research intends to probe the clinical value of combining Sonazoid-contrast-enhanced ultrasound (S-CEUS) quantitative analysis with shear wave elastography (SWE) for discriminating and diagnosing the nature of breast tumors.MethodsA total of 108 breast tumor patients (comprising 120 breast lesions) who were classified as category 4 breast tumor cases and underwent routine ultrasound examinations (June 2022-June 2023) were selected for this study. S-CEUS and SWE examinations were conducted on these breast lesions. The morphological characteristics of S-CEUS were assessed, including morphology (regular, irregular), boundary (clear, unclear), and internal enhancement (no enhancement, homogeneous enhancement, heterogeneous enhancement), along with dynamic enhancement features. Additionally, the maximum Young’s modulus (Emax) from SWE examinations was recorded, and the results were compared to the gold standard in pathology. The diagnostic efficacy of S-CEUS quantitative analysis, SWE alone, or their combined assessment in determining the nature of breast tumors was evaluated.ResultsAmong the cohort of 108 patients, a total of 120 category 4 breast lesions were analyzed, revealing 68 cases (56.67%) of pathologically confirmed malignant breast tumors and 52 cases (43.33%) of benign breast tumors. Malignant breast tumors exhibited irregular morphology, unclear boundaries, heterogeneous internal enhancement, high enhancement levels, increased enhancement ranges, perfusion defects, and predominantly washout-type time-signal intensity curve patterns. These characteristics were significantly more prevalent in malignant tumors compared to benign tumors (p<0.05). Furthermore, quantitative assessment denoted that malignant breast tumors showcased higher CEUS quantitative scores than benign tumors (p<0.05). The Emax for malignant breast tumors was (91.36 ± 24.15) kPa, which was considerably higher than that for benign breast tumors [(49.86 ± 20.31) kPa] (t=9.981, p<0.05). Receiver operating characteristic (ROC) curve analysis demonstrated favorable diagnostic performance in evaluating the nature of breast tumors using S-CEUS quantitative analysis (AUC: 0.845) or SWE alone (AUC: 0.789). Particularly noteworthy was the optimal diagnostic efficacy achieved through the combined assessment of S-CEUS quantitative analysis and SWE (AUC: 0.916), yielding sensitivities and specificities of 95.59% and 80.77%, respectively.ConclusionBoth S-CEUS quantitative analysis and SWE are valuable tools for the evaluation of benign and malignant characteristics in breast tumors. Particularly, their combined application demonstrates superior diagnostic efficacy.